Demographic Uncertainty and Generational Consumption Risk with Endogenous Human Capital - Patrick M. Emerson; Shawn D. Knabb (Institute of Labor Economics (IZA), 2018)
This paper uses a model with overlapping generations to demonstrate that human capital accumulation can potentially attenuate factor price movements in response to birth rate shocks. Specifically, we show that if education spending per child is inversely related to the size of the generation, then there will be less movement in factor prices in response to the relative size of each generation. The degree of this attenuation effect will depend on the effectiveness of education spending in producing human capital. We also demonstrate that this attenuation effect tends to concentrate generational consumption risk around the generation subject to the birth rate shock. In a limiting case, we show that an i.i.d birth rate shock translates into an i.i.d. generational consumption shock. In other words, each generation bears all of the risk associated with their own demographic uncertainty. As a final exercise, we demonstrate that if the tax rate funding education spending varies with the size of the generation rather than education spending per child, then human capital does not influence the dynamic behavior of the economy in response to a birth rate shock.
Keywords: J12; E21; I26; I31; J11; 330; human capital; consumption risk; factor price movements; fertility shocks